Influence of carbide grain size and crystal characteristics on the microstructure and mechanical properties of HVOF-sprayed WC-CoCr coatings. (December 2017) - Wang, Dafeng; Zhang, Boping; Jia, Chengchang; Gao, Feng; Yu, Yueguang; Chu, Ke; Zhang, Mina; Zhao, Xiaolin
Abstract: Nanostructured WC-CoCr coatings play a significant role in industrial sectors including petrochemical and aerospace fields. However, their fracture toughness requirements still need to be further improved because of more decarburization of conventional nano scale WC grains. In the study, three representative types of WC-CoCr powders were selected to illustrate the dependence of the microstructure and mechanical properties of HVOF-sprayed coatings on the carbide grain size and their crystal characteristics in the starting powders. It is demonstrated that the ultrafine powder causes excessive decomposition of the WC phase to W2 C phase when compared to submicrostructured and nanostructured powders, owing to the WC grains with a higher density dislocation. The present study implies the critical role of apparent twin characteristics within WC grains in enhancing the microhardness and fracture toughness of the nanostructured coating. The coating deposited with nanostructured powders exhibits the best comprehensive properties, which include low decarburization, superior microhardness and fracture toughness. Graphical abstract: Fig. 12 Fracture toughness of N, U and S as-sprayed coatings When compared with U and S coatings, N coating exhibits a superior fracture toughness since it is closely related to small amount of porosity and lower decomposition of WC phase into W2 C phase during spraying. Highlights: HVOF WC-CoCr coatings with different carbide crystal characteristics are prepared. Twin microstructure within nano-sized WC grains results in less decarburization. Dislocation within ultrafine WC grains significantly promotes decomposition of WC to W2 C phase. The nanostructured coating has a superior comprehensive mechanical performance.